Associations between high cholesterol and insulin sensitivity in diabetic versus non-diabetic among young adults in Lephalale, Limpopo Province, South Africa - Sigudu, Themba Titus; Mkhatshwa, Thandiwe Ntomfuthi; Monyeki, Kotsedi Daniel; Matshipi, Moloko (Frontiers in Endocrinology, 2025)
BackgroundThe rising global burden of diabetes mellitus and associated metabolic disorders disproportionately affects low and middle-income countries, with dyslipidemia being a key contributor to cardiovascular risk in insulin-resistant individuals. Limited data exist on population-specific associations between cholesterol levels and insulin sensitivity among young adults in transitioning African communities.MethodsThis cross-sectional study analyzed 781 young adults (18–29 years) from the Ellisras Longitudinal Study in Lephalale, South Africa. Participants were stratified by diabetic status using ADA criteria. Fasting blood samples assessed glucose, insulin (HOMA-IR), and lipid profiles. Multivariable linear regression evaluated cholesterol-HOMA-IR associations, adjusted for confounders.ResultsDiabetics (n=169) showed significantly higher total cholesterol (5.1 vs. 4.3 mmol/L), LDL-C (3.2 vs. 2.6 mmol/L), triglycerides (1.8 vs. 1.1 mmol/L), and lower HDL-C (1.0 vs. 1.2 mmol/L) than non-diabetics (all p<0.001). Dyslipidemia prevalence was 2–3 times higher in diabetics (e.g., 52.7% vs. 23.2% for high total cholesterol). HOMA-IR correlated positively with total cholesterol (β=0.42, p<0.001), LDL-C (β=0.38, p<0.001), and triglycerides (β=0.47, p<0.001), and inversely with HDL-C (β=−0.51, p<0.001).ConclusionYoung diabetic adults in Lephalale exhibit pronounced dyslipidemia and insulin resistance, with strong lipid-HOMA-IR associations. Findings highlight the need for early metabolic screening and targeted interventions in transitioning African communities to mitigate future cardio metabolic risk.